(untitled) (Research, Society and Development, 2021)
Objective: to synthesize evidence on the use of realistic simulation as a mediator of the teaching-learning process in the training of pharmacists. Methods: Systematic review and narrative synthesis. Results: The findings show that the use of realistic simulation as a mediator of the teaching-learning process in the education of pharmaceutical professionals provides benefits to academic performance, improving the teaching-learning process, making it easier, contributing to the development of skills and skills in pharmaceutical practice. Conclusion: There is evidence that the use of realistic simulation provides an improvement in satisfaction, performance, and safety with the teaching-learning process; as well as, in terms of skills and abilities, the improvement of the technical management of pharmaceutical assistance, of the clinical management of the medicine, of the practice of pharmaceutical care, of the resolution of problems related to medicines and of empathy for patients as interpersonal relationships.